INCREASING STUDENTS’ UNDERSTANDING OF EARTHQUAKES AND MITIGATION BY UTILIZING CHAVABOT AS LEARNING MEDIA (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2025)
Indonesia's low ranking in PISA is partly due to students' low comprehension skills. Students' understanding provides a strong basis for using the knowledge practically. This study aims to determine the effect of Chavabot as a learning media on students' understanding in learning about earthquake and mitigation as well as students' impression of Chavabot in learning. This research was conducted using a pre-experimental method with a one-group pre-test and post-test design in class 8 at one of the private junior high schools in Bandung with a total of fifty-eight respondents. The instruments used in this study were cognitive tests with 20 multiple-choice questions and a questionnaire consisting of 10 statements. The results of this study showed a significant increase with an α value of 0.000 and N-gain 0.79. The use of Chavabot as learning media showed the highest increase in cognitive domain C1. While the lowest increase was in cognitive domain C2. In addition, Students’ impressions were also positive towards the application of Chavabot. Most students moderately agreed that Chavabot was very helpful in understanding the topic of earthquakes and mitigation.
Keywords: students' understanding; chavabot; students impression; erathquake; mitigation